Alih Kode Pada Teks Lagu Pop Bali Bilingual Kajian Sosiolinguistik - Diah Meita Sari, Ni Putu; Sutama, Putu; Puspawati, Luh Putu (Humanis; Volume 17. No. 1. Oktober 2016, 2016)
Research "Code Switching in the Text of The Balinese Bilingual Pop Songs; The Study of Sociolinguistics" aimed at describing the history of the development of Balinese pop song bilingual, sorts and characteristics instead of code switching, form and direction over the code switching, as well as the factors that led to the code switching. The theory of Sociolinguistics expressed by Nababan (1991) who refers to concepts related to the code switching. In the provision of the data using the method refer and methods of conversation with by record and note the technique with advanced technique, namely classifying data. Phase analysis using the padan method with the selected match method subtypes method padan post-translational.  Presentation of the results  analysis using formal and informal methods with inductive and deductive techniques . Results found in this study is that historically Balinese bilingual pop songs appeared around 1985. The text of the Bali pop songs bilingual has a form similar to the poem, as well as having the functions of communicative function, i.e. the function of the imaginative child, and function of spiritual satisfaction. There is a range of code switching that is  internal code switching and external code switching. Characterized code switching i.e. the language dependency. the form instead of the code switching there is a form of the clause and sentence. Direction code switching there are six i.e code switching from the Balinese language to Indonesia language, code switching from Indonesia language to Balinese language, code switching from the Balinese language to English, code switching from English to Balinese language, code switching from Balinese to the Japanese language, and code switching from the Japanese to the Balinese language. Cause factor code switching is expressly author, interlocutors, the function of pleasure, level one's language proficiency, neutralizes the negative meaning.